Analysis of China’s higher education digitalization strategies - CUI, ZIWEN (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
For the successful fulfillment of the great rejuvenation of the Chinese nation, the digitization of higher education is of particular relevance. This article explains its study worth from the three perspectives of moral composition: quality education, and education ecology, starting from the level of higher education’s digitalization to the national and higher education itself. The steps to be taken for the further digital transformation of higher education will be considered along with the direction and goals of future development. In order to ensure the high development of talents, understand the consequences of the digital age, three new ways for high-end Information Technology to rise to a high level of talent quality education can be explored: promoting the exchange of high-quality resources, reforming training in education sector, and creating a new intellectual educational environment. The transition of higher education to the digital model is a complex, systematic effort that faces new opportunities and obstacles. To achieve comprehensive success, it is important to produce, learn, and conduct scientific research, and put into practice the use of multi-party involvement, methodical planning, collaboration, reform, and innovation.